Phytochemical Characterization and Utilization of Dried Red Beetroot (Beta vulgaris) Peel Extract in Maintaining the Quality of Nile Tilapia Fish Fillet - Hossam S. El-Beltagi; Mohamed M. El-Mogy; Aditya Parmar; Abdallah Tageldein Mansour; Tarek A. Shalaby; Marwa Rashad Ali (MDPI AG, 2022)
Phytochemicals derived from agro-industrial waste materials could be employed as functional food additives and natural antioxidants to replace their synthetic counterparts, which are increasingly being rejected. The current study aims to assess total phenolic compound (TPC), flavonoids, betalain contents, and antiradical scavenging using DPPH and IC50% of dried red beetroot peel (DRBP) extract at different concentrations of 50, 80, 100, 150, and 200 mg/100 mL t. In addition, a characterization of phenols and flavonoids was conducted using HPLC. The second part of this study aims to utilize aqueous DRBP extract in preserving Nile Talipia fish fillet at two concentrations of 80 and 100 mg/100 mL water, compared with 200 ppm of BHT (butylated hydroxytoluene) and control at 5 °C for 10 days. The DRBP aqueous extract was found to have a high concentration of TPC (832 mg/100 g), flavonoids (234 mg/100 g) and betalains (535 mg/100 g) compounds, resulting in a potential antioxidant activity. The IC50% for the extract was detected at 80 mg/100 mL extract. DRBP aqueous extract showed an excellent preservative effect on the fish fillet. Fish fillet samples treated with DRBP extract at a concentration of 100 mg/100 mL were superior in reducing TBA (thiobarbituric acid) increase compared with other treatments at the end of cold storage. Overall, the study showed that red beetroot extracts can act as a natural preservative agent due to their significant antioxidant activity, providing healthy and safe food to consumers.